O papel do curso de licenciatura em educação do campo na reconstrução do modo de vida camponês: a experiência da comunidade São Miguel de Murutinga, Abaetetuba-PA - PANTOJA, Dielly Ribeiro (2019)
This monograph aims to describe the contribution of training in the Field Education of Abaetetuba, in the renaissance of Family Agriculture in the Community of São Miguel de Murutinga, from the construction of projects in this community. The present work describes the situations that this family agriculture has been facing over time, as well as the main factors that have influenced the weakening and destructuring of the peasant way of life. It is also important to discuss the perspective of the formation of the rural education course aimed at rural development, having as a small experience the reality of the farmers of Murutinga. From 2014 to 2018, the experience will be based on the history of the community, participation in public policies and partnership with different governmental and non-governmental institutions, how social movements begin to emerge and interact in the community and how the various aspects: economic, cultural, educational, etc., begin to follow this dynamic through the struggle of family farmers for the guarantee of their rights. Thus, the methodology used was qualitative field research, with applications of semi-structured questionnaires, historical interview. As a conclusion the results obtained in relation to the theoretical and practical training of farmers regarding production systems, social reorganization of the community, rescue of farmers' autonomy, participation of young people in the teaching and learning processes both in relation to the practices developed in the lots as in the development of research by students of the community aiming at social and economic alternatives, partnership with municipal and state institutions and with representatives of cooperatives. Adding suggestions and perspectives, for future actions to be worked and achieved in Family agriculture in the municipality of Abaetetuba, as a second step for rural development.